Adoption of Climate Smart Agricultural Practices by Rice Farmers in Akwa Ibom State, Nigeria - Nsikak-Abasi Etim; Nyaudoh Ndaeyo (Journal La Lifesci, 2020)
The rise in population amidst climate change has exerted undue pressure on food production and security. Rice production has also been adversely affected by rising temperature and varying rainfall resulting in reduced productivity. In order to cope with the negative impact of climate change events on rice production, farmers need strengthen and improve their adaptive capacity. Therefore, a study was conducted to empirically estimate the factors affecting the adoption of Climate Smart Agricultural ( CSA) practices in rice production. Multistage sampling procedure was employed to select the representative rice farmers for the study. With the aid of oral interview and questionnaires, information were elicited from 90 farmers. Data were analyzed using descriptive statistical tools and univariate probit model. Results revealed that majority ( 62.5 percent) of rice farmers were women, 75 percent were married, 67.5 percent were within economically active age and 85 percent had post primary education. Findings further showed that education level of farmers, family size, farm income and access to information on climate change were positively and directly related to rice farmers willingness to adopt climate smart agricultural practices at 1 percent and 5 percent levels of significance respectively. Result also showed that about 55.85 percent of rice farmers in the study location received information on climate change from village meetings, friends, relatives and other farmers. Agricultural policies that aimed at increasing incomes of rice farmers and creating awareness on climate change will be rational decision.